Babaeng nanlaban a critical analysis on how violent female narratives in Philippine cinema counter gendered disinformation - Ansong, Ana Loraine Fabian
This research proposes a critical analysis of the concept of the babaeng nanlaban (woman who fought) in Philippine Cinema. It also discusses the babaeng nanlaban narratives as countervoices against gendered disinformation and violence. Additionally, it seeks to challenge the concept of violence in cinema and redefine it as a retributive counterattack when associated with the character of the empowered female. The research primarily employs a Feminist Critical Discourse Analysis that allows for a critical examination and interpretation of the themes, visual languages and cues, and overall contextualization of the films as mediating tools for empowerment. The study focuses on a selection of films produced from 2016 to 2022, at the Digital Age of Philippine Cinema under the Duterte regime. This time period marked by authoritarian rule, gendered disinformation, and structural violence is key to determining the reimagined image of the empowered female. The research aims to put forward the stories of empowered women as told by actual empowered women filmmakers. It seeks to contribute to the fight against gendered disinformation by providing templates for the recalibration of both scholarship and media.